Optimisation of public bus transport network in Singapore using spatial parameters and demographic information - Liu, Li (2010)
Transportation is an important aspect of our urban daily life. Unfortunately, the performance of urban transport system is getting worse in many cities and traffic causes a lot of negative environmental effects. Developing better public transport and using non-polluting modes are believed to be the way towards sustainable transportation. Effective design of well-planned bus routes and services that are closely integrated with mass rapid transit can increase the attractiveness of public transportations in urban areas and improve its quality.